WRIST AND HAND STRUCTURE: HISTOLOGY AND DISEASE PERSPECTIVE - Baqiyevna, Akbarova Barchinoy; Jumaramziddin Eldorbek o’g’li, No‘monjonov (Journal of Medical Genetics and Clinical Biology, 2025)
The wrist and hand are intricate anatomical structures essential for human mobility, dexterity, and performing daily tasks, comprising bones, muscles, ligaments, nerves, and blood vessels that operate as an integrated system. Diseases affecting these structures, such as tendinitis, arthritis, carpal tunnel syndrome, and osteoarthritis, compromise their function and quality of life, and their diagnosis and treatment increasingly rely on understanding histological changes at the tissue level. Despite the clinical importance of wrist and hand disorders, comprehensive analysis connecting histological features with clinical symptoms and the effectiveness of evolving treatment methods remains limited. This study aims to examine the anatomical and histological structure of the wrist and hand, analyze common diseases from a microscopic perspective, and evaluate contemporary treatment strategies based on recent scientific findings. Histological analysis reveals that inflammation, tissue degeneration, and fibrosis are common pathological features across different wrist and hand diseases, with treatments such as NSAIDs, corticosteroids, hyaluronic acid injections, and regenerative medicine showing promising outcomes. By linking clinical manifestations with underlying histological alterations, this article highlights the role of histology in early diagnosis, individualized treatment planning, and the advancement of novel therapeutic approaches. Enhancing knowledge of histological mechanisms not only improves diagnosis and treatment of wrist and hand diseases but also contributes to developing preventive strategies, ultimately advancing patient care in musculoskeletal medicine.